Spasticity as the First Manifestation of Ischaemic Lesions Involving the Cingulum. (4th November 2013) - Alves, Ivânia; Tedim Cruz, Vítor; Grebe, Hans Peter
Abstract : Background and Purpose . Spasticity is a positive sign of upper motor neuron syndrome that usually develops weeks after a stroke. The mechanisms that lead to its appearance are not completely understood, namely, the cortical regions whose lesion may induce spasticity. Summary of Cases . We report two patients with an ischaemic stroke entailing the anterior cingulate gyrus (pericallosal artery territory), who presented with acute hemiplegia and spasticity since symptom onset. Spasticity resolved within days after onset. Conclusions . The acute destruction of the anterior cingulate region, interrupting inhibitory projections towards lower motor centres, probably explains the acute onset of spasticity that occurred in these two patients. Further studies addressing the role of this region in acute and chronic disturbances of muscular tone are necessary.